Big Five Personality and Workplace Emotions An Integrative Systematic Review - Rita Rosmawati; Eeng Ahman; Janah Sojanah (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study systematically reviews empirical research on the relationship between Big Five personality dimensions and workplace emotions over the past decade, proposes an integrative conceptual framework, and identifies directions for future research. Design/methodology/approach – A Systematic Literature Review (SLR) approach was employed following PRISMA guidelines across four stages: identification, screening, eligibility assessment, and inclusion. Searches were conducted on Scopus, ScienceDirect, SpringerLink, Taylor & Francis Online, and Google Scholar using Boolean keyword combinations. A structured quality appraisal rubric was applied to all eligible articles by two independent reviewers. Finding/Results – From 458 identified articles, 19 met all inclusion criteria. Thematic synthesis reveals consistent patterns: neuroticism is the strongest predictor of negative workplace emotions (stress, anxiety, burnout) mediated by maladaptive emotion regulation; extraversion and agreeableness consistently associate with positive emotions and prosocial interpersonal quality; conscientiousness functions as an emotional buffer, and is the strongest predictor of job performance; and openness to experience supports emotional flexibility, particularly in dynamic environments. Emotion regulation and emotional labor serve as the primary mediating mechanisms. Affective events theory is confirmed as a robust framework for understanding personality–emotion linkages at work. Originality/Value – This study contributes an integrative conceptual framework linking Big Five traits, emotion regulation strategies, and workplace emotional outcomes, with contextual factors as moderators. Practical implications are provided for personnel selection, employee development, and organizational well-being interventions.